Comparison of dentin hardness between conventional drill and chemomechanical methods in primary and permanent dentition using nanoindenter - M Kruthika; K Ramesh; S Shankar; V Suresh Kumar; Arumugam Karthik; P K Sasikumar (Wolters Kluwer Medknow Publications, 2016)
Introduction: Latest theories regarding the rationale of carious dentin removal are beginning to question the amount of tissue that needs to be excavated to successfully treat a carious tooth. It is not always easy to make a decision at which point to stop excavation because there is an apparent lack of objective clinical markers. However, hardness of dentin might be a useful marker in this respect. Nanoindentation test is a variety of indentation hardness test applied to small volumes such as teeth which contain nanosized structures. Aims: To compare and evaluate the nanohardness of dentin after chemomechanical (Carie-care) method of caries removal with the conventional (rotary instrument) method of caries removal in primary and permanent teeth using nanoindenter. Materials and Methods: An in vitro randomized controlled trial was conducted using fifteen primary and fifteen permanent extracted molars with active carious lesion extending into the dentin. The primary and permanent molars were further randomly divided into two subgroups by sectioning the samples into two halves. Caries removal was done using conventional drill (CD) and chemomechanical caries removal (CMCR) (Carie-care) methods. Following the caries removal, the test specimens were subjected for evaluation of nanohardness of dentin using nanoindenter. Student's t-test, analysis of variance, and Bonferroni test were used. Results: Statistically significant difference between the 4 groups with a P < 0.05 was obtained. Conclusions: After caries removal, the hardness of remaining dentin was found to be harder after CMCR method than with the CD method in both primary and permanent teeth, and the remaining dentin of the permanent teeth was found to be harder than the primary teeth after caries removal.